2014
DOI: 10.1158/0008-5472.can-14-0626
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Subpopulations of Head and Neck Cancer Cells with Different Levels of Intracellular Reactive Oxygen Species Exhibit Diverse Stemness, Proliferation, and Chemosensitivity

Abstract: Head and neck squamous cell carcinoma (HNSCC) is driven by cancer-initiating cells (CIC)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 52 publications
2
81
0
5
Order By: Relevance
“…S1C) and tumor sphereforming ability ( Supplementary Fig. S1D), which are typical signs of stem-like population enriched in drug-resistant cells (26). In addition, G9a and the corresponding H3K9 methylations are higher expressed in CR cells than the parental cells (Fig.…”
Section: G9a Expression Is Associated With Poor Chemotherapeutic Respmentioning
confidence: 90%
“…S1C) and tumor sphereforming ability ( Supplementary Fig. S1D), which are typical signs of stem-like population enriched in drug-resistant cells (26). In addition, G9a and the corresponding H3K9 methylations are higher expressed in CR cells than the parental cells (Fig.…”
Section: G9a Expression Is Associated With Poor Chemotherapeutic Respmentioning
confidence: 90%
“…Similarly, ROS low cells in head and neck cancers express CSC markers and have enhanced tumor-initiating capacity. ROS low cells are enriched after cisplatin treatment and inhibition of antioxidant systems in these cells sensitizes them to the drug (46). Aldehyde dehydrogenase (ALDH) proteins can function as antioxidants by controlling the oxidation of a variety of aldehydes, including toxic byproducts generated by ROS (47).…”
Section: Metabolic Heterogeneitymentioning
confidence: 99%
“…However, recent evidence showed that the upregulation of antioxidant protein Nrf2 might promote survival and resistance to therapies in cancer cells (34). A subpopulation of HNSCC cells carrying low ROS may exhibit more stemness and chemoresistance properties (35).…”
Section: Introductionmentioning
confidence: 99%